PEMELIHARAAN MENGGUNAKAN PLATFORM WICOPE PADA UNIT VOLVO FMX 440 DI PT. BUKIT MAKMUR MANDIRI UTAMA - Matarru, Andre Amba; Ridoh, Ahmad (Jurnal Energi Dan Manufaktur; Vol 15 No 2 (2022)DO - 10.24843/JEM.2022.v15.i02.p09, 2023)
One of the supporting mining activities at PT. Bukit Makmur Mandiri Utama is the maintenance of the truck vehicle unit, where the truck functions as a mode of transportation to transport various kinds of materials and other materials including fuel. The unit operates continuously causing a decrease in the level of reliability and causes frequent breakdowns and high downtime in mining units, including the Volvo FMX 440 truck unit. To minimize breakdown and downtime, a good maintenance system is needed to prevent engine damage. Scheduled maintenance systems or predictive maintenance using the Wicope Platform can minimize breakdown conditions. In order to obtain a maintenance mechanism that can increase the service life of a unit and component, it can also have an effect on saving the company's expenses in carrying out the maintenance process.